2020
DOI: 10.1053/j.gastro.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intestinal Microbiota of Children With Celiac Disease at the Time of Diagnosis and on a Gluten-free Diet

Abstract: BACKGROUND AND AIMS: It is not clear whether alterations in the intestinal microbiota of children with celiac disease (CD) cause the disease or are a result of disease and/or its treatment with a gluten-free diet (GFD). METHODS: We obtained 167 fecal samples from 141 children (20 with newonset CD, 45 treated with a GFD, 57 healthy children, and 19 unaffected siblings of children with CD) in Glasgow, Scotland. Samples were analyzed by 16S ribosomal RNA sequencing, and diet-related metabolites were measured by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 46 publications
(62 reference statements)
9
59
1
Order By: Relevance
“…Alternatively, celiac disease is an autoimmune destruction of the villi of the small intestine triggered by gluten in genetically susceptible individuals, causing nutrient malabsorption, leading to intestinal and extra-intestinal symptoms, and a gluten-free diet (GFD) for life the only treatment. The pathogenesis is multifactorial, and although genetic predisposition occurs in 30% - 40% of the general population, only a small proportion of these individuals will develop the disease, suggesting the importance of environmental factors, with recent evidence supporting the participation of GM ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, celiac disease is an autoimmune destruction of the villi of the small intestine triggered by gluten in genetically susceptible individuals, causing nutrient malabsorption, leading to intestinal and extra-intestinal symptoms, and a gluten-free diet (GFD) for life the only treatment. The pathogenesis is multifactorial, and although genetic predisposition occurs in 30% - 40% of the general population, only a small proportion of these individuals will develop the disease, suggesting the importance of environmental factors, with recent evidence supporting the participation of GM ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This ICAM is also expressed on intestinal T cells in patients with CD and is thought to be an immune system strategy to modulate the inflammatory process. To close the circle of therapeutics and resultant microbiome changes suggested by the researchers in the current study, 1 it has also been shown that a gluten-free diet can restore B-defensins to their normal level, but paradoxically, a gluten diet can elevate these levels in a nonhuman primate, attesting to the often conflicting results seen in this area of research endeavors. 6 Bridging the mechanistic gap between diet, PC effects, and the microbiome should be the direction taken by future CD research.…”
mentioning
confidence: 56%
“…We read with great interest the comprehensive article of Zafeiropoulou et al 1 describing the mechanics of microbiome change in treated and untreated Scottish children with celiac disease (CD), both crosswise and longitudinally, ascribing the changes to dietary treatment. We do not necessarily disagree with their tentative conclusion but would like to highlight the potential intermediary players that may modulate the microbiome.…”
mentioning
confidence: 99%
“…A recent analysis of the gut microbiota and diet-related metabolites in a large cohort of children affected with CeD revealed specific microbiota signatures for both untreated individuals with new-onset CeD and individuals treated with GFD, with respect to the healthy controls ( 276 ). The authors confirmed the overabundance of the microbiota taxa mentioned above, such as Bacteroides .…”
Section: Celiac Diseasementioning
confidence: 99%
“…The reduction in Megamonas , Ruminococcus , and Holdemanella was recognized as a consequence of the treatment with GFD. Importantly, the authors identified a lower abundance in 11 specific bacterial taxa considered as biomarkers of CeD, with Clostridium sensu stricto 1 as the most influential one ( 276 ).…”
Section: Celiac Diseasementioning
confidence: 99%